Diversity of Gastropods in the Intertidal Zone of Tanjung Air Panas Beach, Tulehu Village, Central Maluku Regency, Indonesia - Pattikawa, Jesaja Ajub; Hulopi, Mahriyana; Uneputty, Prulley Annette; Siahainenia, Laura; Tawainella, Ilfayeni Salsabillah (Universitas Pattimura, 2025)
Research on the diversity of gastropods in the intertidal area of ​​Tanjung Air Panas Beach, Tulehu Village, Central Maluku Regency was conducted in November 2024. Gastropod samples were collected in 60 quadrants on 5 belt transects. All individuals obtained were identified to the species level and the number of individuals was counted. The results of the study showed that gastropods in the intertidal area of ​​Tanjung Air Panas Beach, Tulehu Village consisted of 9 species belonging to 1 subclass i.e. Caenogastropoda, 3 orders, namely Caenogastropoda, Littorinimorpha and Neogastropoda, 7 families and 8 genera. Nassarius globosus had the highest occurrence frequency and was found in all transects and all quadrants (100%), followed by Conus ebraeus which was found in 6 quadrants (10%) and then Canarium microurceus which was found in 4 quadrants (6.67%). The highest density is owned by N. globosus with 2,633 ind./m2 (87.78%) then followed by C. ebraeus with 0.117 ind./m2 (3.89%) and C. microurceus with 0.100 ind./m2 (3.33%). The Shannon diversity index (H’), Simpson dominance index (D) and Shannon uniformity index (E) are 0.59, 0.77 and 0.27, respectively. Based on the three indices, it can be concluded that the gastropod community in the intertidal area of ​​Tanjung Air Panas Beach, Tulehu Village has low diversity and uniformity with high dominance.